Charge transfer reactions between gas-phase hydrated electrons, molecular oxygen and carbon dioxide at temperatures of 80–300 K. Issue 34 (8th August 2016) - Akhgarnusch, Amou; Tang, Wai Kit; Zhang, Han; Siu, Chi-Kit; Beyer, Martin K.
Abstract : With a combination of mass spectrometry and quantum chemistry, we derive hydration enthalpies for CO2 ˙ − and O2 ˙ − and show that the charge transfer from CO2 ˙ − to O2 proceeds via a CO4 ˙ − intermediate. Abstract : The recombination reactions of gas-phase hydrated electrons (H2 O) n ˙ − with CO2 and O2, as well as the charge exchange reaction of CO2 ˙ − (H2 O) n with O2, were studied by Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry in the temperature range T = 80–300 K. Comparison of the rate constants with collision models shows that CO2 reacts with 50% collision efficiency, while O2 reacts considerably slower. Nanocalorimetry yields internally consistent results for the three reactions. Converted to room temperature condensed phase, this yields hydration enthalpies of CO2 ˙ − and O2 ˙ −, Δ H hyd (CO2 ˙ − ) = −334 ± 44 kJ mol −1 and Δ H hyd (O2 ˙ − ) = −404 ± 28 kJ mol −1 . Quantum chemical calculations show that the charge exchange reaction proceeds via a CO4 ˙ − intermediate, which is consistent with a fully ergodic reaction and also with the small efficiency. Ab initio molecular dynamics simulations corroborate this picture and indicate that the CO4 ˙ − intermediate has a lifetime significantly above the ps regime.